Pengaruh Kompetensi Pedagogik, Profesional, dan Sosial Guru terhadap Kualitas Pembelajaran - Soleha; Rahmat Rizki Atqiya; Muhammad Nurul Hikam Annafis; Munawir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Abstract: This study aims to describe teacher professionalism based on pedagogical, professional, and social competencies and their contribution to improving learning quality. The research employs a qualitative approach using a systematic literature review method. Data were collected from relevant books, scientific journals, and academic documents, then analyzed through descriptive techniques, including data reduction, comparison, and interpretation. The findings indicate that pedagogical competence plays a dominant role in determining the effectiveness of learning. Teachers with strong pedagogical skills are able to design interactive learning, apply varied teaching methods, and create conducive classroom environments that enhance student engagement and learning motivation. However, weaknesses were identified in formative assessment practices, which indicate an incomplete learning evaluation cycle. In terms of professional competence, teachers generally demonstrate adequate mastery of subject matter. Nevertheless, difficulties remain in contextualizing learning materials to real-life situations, which limits the meaningfulness of instruction. Meanwhile, social competence contributes significantly to creating positive learning environments through effective communication, empathy, and collaboration. However, interaction with parents and collaboration among teachers are still not fully optimized. Overall, the study highlights that teacher competence is a multidimensional construct in which pedagogical competence serves as the core driving factor, while professional and social competencies function as supporting elements. The imbalance among these competencies suggests a gap between theoretical expectations and classroom practice. Therefore, integrated professional development and continuous training are essential to enhance teacher competence and improve overall educational quality.